2013
DOI: 10.1590/1414-431x20122616
|View full text |Cite
|
Sign up to set email alerts
|

Rat vas deferens SERCA2 is modulated by Ca2+/calmodulin protein kinase II-mediated phosphorylation

Abstract: Ca2+ pumps are important players in smooth muscle contraction. Nevertheless, little information is available about these pumps in the vas deferens. We have determined which subtype of sarco(endo)plasmic reticulum Ca2+-ATPase isoform (SERCA) is expressed in rat vas deferens (RVD) and its modulation by calmodulin (CaM)-dependent mechanisms. The thapsigargin-sensitive Ca2+-ATPase from a membrane fraction containing the highest SERCA levels in the RVD homogenate has the same molecular mass (∼115 kDa) as that of SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…The molecular evidence for Ca 2+ homeostasis on rat vas deferens function has been demonstrated previously: (1) subcellular fractions obtained from rat vas deferens homogenate contain vesicles of SR origin presenting SERCA pumps, RyR and IP 3 R 18 ; (2) the isoform of the SERCA pump expressed in rat vas deferens is probably SERCA2b 11,19 ; and (3) treatment at 37°C and pH 7.4 is sufficient to dissociate the FKBP12-CRC complex in rat vas deferens 12 . The aim of this work was to demonstrate the effect of ivermectin on Ca 2+ -ATPase activity and Ca 2+ content of SR vesicles of rat vas deferens in the presence or in the absence of FKBP12-CRC complex.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The molecular evidence for Ca 2+ homeostasis on rat vas deferens function has been demonstrated previously: (1) subcellular fractions obtained from rat vas deferens homogenate contain vesicles of SR origin presenting SERCA pumps, RyR and IP 3 R 18 ; (2) the isoform of the SERCA pump expressed in rat vas deferens is probably SERCA2b 11,19 ; and (3) treatment at 37°C and pH 7.4 is sufficient to dissociate the FKBP12-CRC complex in rat vas deferens 12 . The aim of this work was to demonstrate the effect of ivermectin on Ca 2+ -ATPase activity and Ca 2+ content of SR vesicles of rat vas deferens in the presence or in the absence of FKBP12-CRC complex.…”
Section: Introductionmentioning
confidence: 75%
“…Finally, our group recently demonstrated that chronic malnutrition affected several components related to intracellular Ca 2+ handling in vas deferens, reducing the haploid cell count in this organ and decreasing the reproductive capacity of the male adult Wistar rats 6 . [7][8][9][10][11] . Both the efflux and the influx of Ca 2+ from intracellular stocks are well regulated by the 12 kDa FK506 Binding Protein (FKBP12), an immunophilin located in the cytoplasm of cells, that is the pharmacological receptor for the immunosuppressant drugs FK506 (tacrolimus) and rapamycin 12 .…”
Section: Introductionmentioning
confidence: 99%